Clinical features of late-onset circulatory dysfunction in premature infants - Koyama N; Kouwaki M; Tanaka T; Ohki S; Iwase K; Terasawa S; Miyaji M; Iwaki T; Kokubo M; Kobayashi S; Mizuno H; Fujimoto S; et al. (Dove Medical Press, 2014)
Norihisa Koyama,1 Masanori Kouwaki,1 Taihei Tanaka,2 Shigeru Ohki,3 Kazuhiro Iwase,4 Shunichi Terasawa,5 Masanao Miyaji,6 Toshimitsu Iwaki,7 Minoru Kokubo,8 Satoru Kobayashi,9 Haruo Mizuno,10 Shinji Fujimoto,10 Hajime Togari10 1Department of Pediatrics, Toyohashi Municipal Hospital, Toyohashi, 2Department of Pediatrics, Nagoya Daini Red Cross Hospital, Nagoya, 3Department of Pediatrics, Seirei Hamamatsu General Hospital, Hamamatsu, 4Department of Pediatrics, Nagoya City West Medical Center, Nagoya, 5Department of Pediatrics, Ichinomiya Municipal Hospital, Ichinomiya, 6Department of Pediatrics, Shizuoka Saiseikai General Hospital, Shizuoka, 7Department of Pediatrics, Gifu Prefectural Tajimi Hospital, Tajimi, 8Department of Pediatrics, Kainan Hospital Aichi Prefectural Welfare Federation of Agricultural Cooperatives, Yatomi, 9Department of Pediatrics, Seirei Mikatabara General Hospital, Hamamatsu, 10Department of Pediatrics, Neonatology and Congenital Disorders, Nagoya City University Graduate School of Medical Sciences, Nagoya, Japan Background: Sudden unpredictable hypotension during the post-transitional period, termed late-onset circulatory dysfunction (LCD) of premature infants, has been reported in low birth-weight infants who overcame major problems during the early neonatal period. We investigated the clinical features of LCD and factors associated with the occurrence of LCD. Methods: A multicenter retrospective case-control study. The clinical records of 1,004 children born at less than 32 weeks of gestation were reviewed. Patients with LCD were compared with age-matched non-LCD controls. Results: Of the 1,004 infants, 73 (7.3%) were diagnosed with LCD, with the incidence differing significantly among institutions (P<0.0001). The median age of diagnosis was 16 days of age (range: 4–50 days) and 29 weeks of postmenstrual age (range: 25–35 weeks). The incidence of LCD was inversely correlated with gestational age at birth, except at 22 and 23 weeks. Compared with the control infants, the LCD infants had significantly higher incidences of birth by cesarean section (61/73 versus 48/73, P<0.05); hyponatremia (sodium ,130 mEq/L) at the time of diagnosis (24/66 versus 3/39, P<0.01); deterioration of respiratory status within 24 hours before diagnosis (36/73 versus 6/73, P<0.0001); and periventricular leukomalacia (14/73 versus 4/73, P<0.05). Corticosteroids were effective in 52 infants who were unresponsive to volume expansion or inotropic agents. None of these infants died of LCD. Conclusion: LCD is common but worthy of attention due to its association with periventricular leukomalacia. A review of institutional differences in treatment policies may contribute to the prevention of LCD. Keywords: late-onset circulatory dysfunction of premature infants, low birth-weight infant, shock, adrenocortical insufficiency, periventricular leukomalacia